2022
DOI: 10.1159/000521213
|View full text |Cite
|
Sign up to set email alerts
|

Transitions in Social Network Types over Time among Older Adults

Abstract: <b><i>Objective:</i></b> Network typology studies have identified heterogeneous types of older adults’ social networks. However, little is known about stability and change in social network types over time. We investigate transitions in social network types among older adults, aged 60 years and older, and factors associated with such transitions. <b><i>Methods:</i></b> We used data on 1,305 older adults, participating in 2 waves of a national, longitudinal survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 52 publications
(121 reference statements)
2
12
0
1
Order By: Relevance
“…First, all of the social network variables were dichotomized. The dichotomization of study variables has been a common approach used to facilitate model identification and interpretation in LCA and LTA (Cheng et al, 2021; Rinne et al, 2017; Sung et al, 2022). However, future studies should use different set of standards to categorize the social network variables to better understand the transition patterns of social networks among older adults.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…First, all of the social network variables were dichotomized. The dichotomization of study variables has been a common approach used to facilitate model identification and interpretation in LCA and LTA (Cheng et al, 2021; Rinne et al, 2017; Sung et al, 2022). However, future studies should use different set of standards to categorize the social network variables to better understand the transition patterns of social networks among older adults.…”
Section: Discussionmentioning
confidence: 99%
“…This study found five social network types of diverse, unmarried and diverse, extended family, immediate family, and restricted (Sung et al, 2022). While this study findings serve as an important first step to understanding different social network types, cultural beliefs and societal roles among Singaporean older adults may be different from older adults in the United States (Sung et al, 2022). In addition, Sung et al (2022) acknowledged as a limitation that examining transitions in social networks within the 2-year time span may be subtle (Sung et al, 2022).…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations